(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Dear LAJSBA readers, as you might be aware, we have been appointed as Editor (Ernesto Schwarz) and Associate Editor (Diana G. Cuadrado) of the journal for the period 2014-2016, and the publication of the 21-1 Volume is a good excuse to address you for the first time. First of all, we would like to thank the Board of the Asociación Argentina de Sedimentología for honoring us with this gratifying, but at the same time, challenging task. We will work hard to persist in the path that previous editorial teams have set for this journal. That is to say, to continue positioning LAJSBA as one of the more relevant journals for disseminating the sedimentology and basin analysis-related science that is developed in South America. We feel that Volume 21-1 is a nice example of this, having contributions from Brazil, Chile and Argentina, and ranging from Precambrian successions to modern systems.